Local Organizations: Viable Mechanism for Ensuring Participation in Rural Development - Nepal, Pashupati (Tribhuvan University Journal, 2010)
Local organization was overlooked in development theories for a long time mainly because of the technocratic understanding of development. But this situation did not exit for a long time. Development planners began to search the causes of unsatisfactory result of past development strategies and formulated new strategies that enhance local organized efforts. The organizations lie beyond the government play active role in rural development relative to government organization. Local organization is an important mechanism for involving people in rural development. The most essential local resource in any development activities is the people themselves who, along with their mutual cooperation, transform shapeless materials into useful commodities using skills, intelligence and labour. People can influence the decisions through their joint efforts and common voice. Organization provides ownership to local people in development activities and ensures fair share of benefits. In this context, this article aims to analyze local organizations as viable mechanisms for insuring participation in rural development. Key words: Local organizations; Viable Mechanism; Rural development Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 55-68